2015
DOI: 10.1016/j.appet.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Increased 24-hour ad libitum food intake is associated with lower plasma irisin concentrations the following morning in adult humans

Abstract: Background The relationship between food intake and irisin concentrations in humans is unclear. Objectives To determine whether the previous day’s intake impacts fasting plasma irisin concentrations, or whether fasting irisin concentrations associate with subsequent ad libitum food intake. Methods Sixty-six nondiabetic adults (42 men) were admitted for a study of the determinants of energy intake. After 6 days of a weight maintaining diet, ad libitum energy intake over 3 days was assessed using a vending m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…Irisin concentrations have been shown to be positively associated with fruit but negatively correlated to meat consumption [ 40 ], whereas in another study irisin was not affected by food intake [ 41 ]. It has also been shown that an increasing calorie intake is associated with lower irisin concentrations [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Irisin concentrations have been shown to be positively associated with fruit but negatively correlated to meat consumption [ 40 ], whereas in another study irisin was not affected by food intake [ 41 ]. It has also been shown that an increasing calorie intake is associated with lower irisin concentrations [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only one study in individuals who did not have T2DM showed an association between higher pre-nocturnal energy intake and lower fasting levels of irisin the following morning 106 . However, levels of irisin during fasting did not predict subsequent energy intake, indicating that irisin probably does not regulate appetite in these individuals 106 .…”
Section: Effects On Glucose Homeostasismentioning
confidence: 99%
“…Some studies report that irisin is not affected by food intake [157], while others indicate that irisin levels are positively associated with increasing fruit intake and negatively associated with meat consumption [158]. Finally, an inverse association between irisin and higher caloric intake has been shown [159]. …”
Section: Muscle Released Compoundsmentioning
confidence: 99%
“…Contrasting data on higher or lower serum irisin levels in relation with metabolic disorders, diet and exercise are worth further investigation and could be mostly due to the inaccuracy and lack of standardization of commercially-available ELISA assays. Mechanisms underlying the protective metabolic effects of irisin are not well understood and seem to be mostly related to higher induced energy expenditure and not to anti-inflammatory activities, such as NF-κB inactivation [157,158,159]. …”
Section: Muscle Released Compoundsmentioning
confidence: 99%